Psychological resilience and its relationship to coping with psychological stress strategies among a sample of battered women who benefited from a single service or multi-sectoral services in the North Governorate. (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed at identifying the relationship between psychological resilience and the strategies and approaches of dealing with psychological stress for a sample of abused women who benefited from one or multi-sectorial service/s in North Gaza. The study sample consists of 240 abused women who visited one of the health community centers and was registered as ‘beneficiary’ after receiving services from the center’s clinics. To achieve the results of the study, the researcher used the explanatory analytical descriptive methodology by applying the study to a non-systematic random sample. The researcher used Psychosocial Resilience Measurement Index of the researcher – (Translated: Elian and Alkahlout, 2016), and Strategies and Methods of Coping with stress for the researcher – (Nabila Abu Habib, 2010).Study Key Findings:·  The results showed statistically significant differences of the levels of psychosocial resilience, and all its prompts, for respondents who received one service and respondents who received multi-sectorial support services for the favor of those who received multi-sectorial services (psychosocial, social, legal, police, economic, health, and livelihood). Noting that there were no clear statistically significant differences for shelter services. This does not mean that shelter services are not important, however, the researcher believes that this is maybe since the respondents do not need shelter as they own their own, or this is in reference to other characteristics for abused women who have psychosocial resilience but need other multi-sectorial support like psychosocial, social, or livelihood as a priority. ·  The results showed that the level of psychosocial resilience among respondents who received one service was 55.9%, which is significantly less than those who received multi-sectorial services who had a 63.7% psychological resilience index.·  The results indicated that there were statistically significant differences between the average overall score of psychological resilience attributed to the type of violence; when it was less for women who were subjected to psychological and sextual violence compared to women who were subjected to physical violence, forced marriage, child marriage, deprivation from resources, and/or being subject to more than one type of abuse. ·  The results indicated that there were statistically significant differences between the average overall score of psychological resilience attributed to the type of service; where it was less for women who received psychosocial support services compared to women who received social, police, economic, livelihood, and/or more than one service.·  The results indicated that there were statistically significant differences between the average overall score of psychological resilience attributed to the type of activity. The study showed that women who received more than one activity like individual activities, group activities, awareness activities, couple meetings, and psychosocial consultations had higher scores than women who received one activity.·  The results showed that there was no statistically significant variance for the average strategies of coping with stress between respondents who received one service and respondents who received multi services, except for ‘denial strategy’ and ‘requesting emotional support strategy’. Respondents’ who received one service had more variances under ‘denial strategy’ while for the ‘requesting emotional support strategy’ it was higher for respondents who received more multi services.·  The study results showed that ‘social support strategy’ had the highest relative weight of 57.4% for respondents who received one service, while ‘requesting psychosocial and emotional support’ strategy with a relative weight of 59.2% was the most strategy for coping with stress for respondents who received multi service, while ‘denial strategy’ was the least used strategy in dealing distress for women who received one service an women who received multi services with respective relative weights of 37.3% and 35.5%.·  There are statistically significant differences between the average total score of the level of the following psychological stress coping strategies: (positive re-evaluation, mental distraction, focus and emotion, denial, sarcasm, preoccupying the mind with thinking, planning) attributed to the type of violence, while there are no statistically significant differences between the average psychological stress coping strategies of the following strategies: (social support, active effective dealing, spiritual adaptation, behavioral withdrawal, control of nerves, seeking emotional support, acceptance).·  The results indicated that there are no differences for all coping with stress strategies attributed to the type of service, except for the ‘active effective dealing’ strategy; where it was higher for women who received livelihood services compared to women who received psychosocial, social, legal, health, police and economic services. ·  The results indicated that there are no statically significant differences for all strategies of coping with stress attributed to types of services, except for the ‘behavioral withdrawal’ and ‘preoccupying the mind with thinking’ strategies; where ‘behavioral withdrawal’ were less for women who received group activities, couple meetings, advocacy campaigns, global occasions, recreational events, trainings, and more than one activity compared to women who received individual activity. ·  There is no relationship between strategies for coping with stress and psychological resilience among abused women, except for the strategies of focus, emotion, sarcasm, and acceptance, where there is a significant direct positive relationship between these strategies and the psychological resilience among abused women.·  For ‘positive re-evaluation’ and ‘mental distraction’ strategies, it was higher for child marriage compared to rape, forced marriage, deprivation from resources, and psychological and emotional abuse. For ‘focus’, ‘getting emotional’, and ‘deprivation from resources’ strategies, it was higher for ‘deprivation from resources’ and being subject to more than one abuse. ‘denial’ strategy was higher for being subject to more than one type of abuse rather than being attributed to one type of abuse of physical abuse, child marriage, deprivation from resources, and emotional abuse. Results also indicated that ‘sarcasm’ strategy was higher for physical abuse and for being subject to more than one type of abuse than child marriage, deprivation from resources, and emotional abuse. For ‘reoccupying the mind with thinking’ strategy was higher for child marriage compared to other types of abuse. Lastly, for ‘planning’ strategy was higher when the respondent is subjected to more than one type of abuse of physical abuse, sexual abuse, and forced marriage.
Keywords: Psychological Resilience; Methods and Strategies for Coping with Psychological Stress; Abused Women; Multi-Sectoral Services